Uncovering Malaysian students’ motivation to learning science - Talib, Othman; Wong, Su Luan; Azhar, Shah Christirani; Abdullah, Nabilah (Eurojournals, 2009)
This paper aims to highlight two pertinent points relating to science education in Malaysia; first identifying aspects underlying students’ motivation to learning science, and second outlining the profile of performance indicators leading towards successful science learning among upper secondary students in Malaysia. It is acknowledged that good science learning outcome does not only rely on the way teaching is carried out but also on other factors such as students’ ability and talent, language proficiency, and the right attitude toward science learning, just to name a few. Nonetheless, little do we know the extent to which these factors contribute towards students’ successful science learning. Through preliminary yet in-depth interviews with students, teachers and panel of experts, the researchers list various factors that influence science learning outcomes. Information pertaining to these factors is then used to develop a comprehensive yet psychometrically sound inventory that will help assess students’ potential to excel in science.